PENERAPAN MODEL PENGAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 25 PEKANBARU - Fauziah, Fauziah; Munjiatun, Munjiatun; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : This study in the background by the percentage of the number of students who achieve KKM 75 on exam even semester 2014 - 2015 is even lower. Of the 31 students only 13 (42%) of students who reach KKM and 18 person (58%) students who have not reached KKM with an average of 65.64. This is because teachers rarely used learning models during process the learn teach in the classroom, teachers more much used the lecture method, the teacher does not use props, the teacher did not do the experiment, less involving students in the learning process. Of these problems need to be done to implement the action research model of direct instruction to improve learning outcomes IPA SD Negeri 25 Pekanbaru. The application of direct teaching model is a model of learning that focuses on mastery of concepts and behavior change with a deductive approach, the teacher's role is very important in the direct teaching model so that the learning objectives can be understood by students. With the direct teaching is expected to motivate students to study science so that the material can be controlled well and can improve learning outcomes especially science subjects. To support learning outcomes both in direct teaching, educators must also conduct experiments. Where the research was in SD Negeri 25 Pekanbaru with research subjects are students of class III of 31 people, male students and 18 female students 13 people. This study was carried in 2 cycles. Instrument collecting data in this study is the observation sheet teacher activity, student activity observation sheet and test sheet daily tests. Observations indicate that the activity of teachers and students has increased. The activities of teachers in the first cycle both categories increased 72.22% in the second cycle into 91.66% excellent category. Activity of students in the first cycle both categories increased 69.44% in the second cycle into 91.66% excellent category. The results showed that the learning outcomes of students has increased, the base score with an average of 65.54 incomplete categories increased in the first cycle to 75 categories completed, and the second cycle increased to 80.32 category completely. Classical mastery in the first cycle showed that 74.19%, on the second cycle increased to 87.09% and the percentage of classical completeness predetermined. From the above shows that through the implementation of direct teaching can improve learning outcomes IPA Elementary School third grade students Lesson 25 Pekanbaru years 2014-2015. Based on the results of data analysis and discussion that has been carried out it can be concluded that the application of the model of direct teaching can improve learning outcomes IPA third grade students of SD Negeri 25 Pekanbaru, namely an increase in activity of teachers and students in each cycle, the improvement of learning outcomes IPA, and can achieve mastery student learning as expected.Keywords: direct teaching, learning outcomes IPA